DOUBLE MOVEMENT: HERMENEUTIKA ALQURAN FAZLUR RAHMAN - Vicky Izza (Jurnal Keislaman, 2021)
This study aims to analyze two types of interpretation in the double movement theory presented by Fazlur Rahman in his hermeneutical interpretation. As well as its application to the verses of the Koran related to pluralism, inclusivism, and polygamy. By using a qualitative methodology with the type of library research on the interpretation analysis presented by Fazlur Rahman, conclusions and results were found that there was a difference between Fazlur Rahman's interpretation and the interpretation of his predecessors. Despite the disagreements above, Fazlur Rahman's idea about the importance of contextual interpretation which he formulated in what he called double movements was too valuable not to be appreciated. While the various shortcomings as raised by several commentators as described above, it is our duty to complete them.